A class B scavenger receptor mediates antimicrobial peptide secretion and phagocytosis in Chinese mitten crab (Eriocheir sinensis). (February 2020) - Tang, Muxue; Li, Xuejie; Yang, Lei; Wang, Qun; Li, Weiwei
Abstract: Scavenger receptors (SRs) are pattern recognition receptors (PRRs) vital for innate immunity. As well as their importance in immune recognition, microbe phagocytosis, and the clearance of modified endogenous molecules, they also activate downstream immune responses as co-receptors. In the current study, we identified a class B scavenger receptor in Eriocheir sinensis ( Es SR-B2). The full-length gene is 2, 517 bp and encodes a 517 amino acid polypeptide. Es SR-B2 is expressed widely in all tested tissues and is induced by microbial stimulation. Recombinant Es SR-B2 binds to bacteria and pathogen-associated molecular patterns in vitro . Upon knockdown of Es SR-B2 and bacterial challenge with Staphylococcus aureus or Vibrio parahaemolyticus, phagocytosis rates in hemocytes are decreased. Moreover, the expression of several antimicrobial peptides (AMPs) in response to distinct microorganism stimulation is decreased following Es SR-B2 silencing. Thus, Es SR-B2 is a PRR that protects E. sinensis against invading pathogens by promoting phagocytosis and enhancing AMP expression. Highlights: Es SR-B2 is upregulated in hemocytes upon bacterial stimulation. Es SR-B2 participates in antimicrobial peptide secretion. Es SR-B2 promotes phagocytosis against bacterial invasion.